(7n-2)(5n-6)=0

Simple and best practice solution for (7n-2)(5n-6)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (7n-2)(5n-6)=0 equation:



(7n-2)(5n-6)=0
We multiply parentheses ..
(+35n^2-42n-10n+12)=0
We get rid of parentheses
35n^2-42n-10n+12=0
We add all the numbers together, and all the variables
35n^2-52n+12=0
a = 35; b = -52; c = +12;
Δ = b2-4ac
Δ = -522-4·35·12
Δ = 1024
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:
$n_{1}=\frac{-b-\sqrt{\Delta}}{2a}$
$n_{2}=\frac{-b+\sqrt{\Delta}}{2a}$

$\sqrt{\Delta}=\sqrt{1024}=32$
$n_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(-52)-32}{2*35}=\frac{20}{70} =2/7 $
$n_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(-52)+32}{2*35}=\frac{84}{70} =1+1/5 $

See similar equations:

| 3n−2=1 | | (1)/(5)a=5 | | -5(x+4)=-50 | | -6+x/2=8 | | 0=13-4(8-5n | | 5x+4,7x−2,8x−5=180 | | 9x+2=190 | | -4+5x=x-11+5x | | 6x+7(6+1x)=94 | | 5(-p+5)=-6p | | 5-3(6x-4)=4+8-10x | | -10x-208=89-x | | 116+6b+3+31=180 | | 2-y/5-3=5 | | 2+4v=-12 | | 5(2x+4)=5x+20 | | -56=8(x-3) | | -2x+2-x+3=-1 | | 90+5x-15+30=180 | | 2(2x+64)-98=90 | | 8x+0=7x+2 | | 9a+13-4a=12+5a-3 | | (14x+58)(10x+50)=180 | | 21/5=105/m | | 1/2m-5=11 | | x=29+41 | | 6x-9x=-7=-3x+3-7 | | 5x+1+62°=18x-11 | | 30x-5=6(5x-2) | | 3(s+5)+1=+9 | | 7(3x+2)=20x | | -7m-6m+13=-13m+2 |

Equations solver categories